Dimensional analysis of direct contact condensation induced thermal stratification in a scaled-down suppression pool - Lee, Daehyeong; Han, Ilyoung; Lee, Ulim; Chai, Jangbom; Lee, Chee Ho; Okamoto, Koji; Kim, Tae Yun; Jo, Byeongnam (International Conference on Nuclear Engineering, Proceedings, ICONE, 2019)
This study aimed to experimentally reproduce the thermal stratification induced by direct contact condensation in a scaled-down suppression pool of Fukushima Daiichi nuclear power plants. Furthermore, dimensional analysis was also performed to suggest a criterion for the formation and disappearance of thermal stratification using a modified Richardson number. Steam condensation experiments were carried out to emulate the reactor core isolation cooling in the Fukushima accidents using a blow-down type steam injection pipe. To examine the effects of the steam flow rate on the thermal stratification behaviors, the steam flow rate varies from 0.93 to 3.71 kg/h. In results, thermal stratification was observed by steam condensation in the suppression pool. The time evolution of temperature behaviors (vertical temperature profile in the suppression pool) was compared to results of the sparger type steam injection pipe. Based on the steam bubble images obtained by a high-speed-camera during the experiments, the modified Richardson number which was defined as the ratio of buoyancy to inertia force of steam bubbles was calculated in periodic time intervals. The formation and disappearance of the thermal stratification caused by direct contact condensation was explained by the change of the modified Richardson number, in which the criterion of the modified Richardson number was suggested to be around one.
Keywords: Dimensional analysis; Direct contact condensation; Fukushima accidents; Fukushima dai-ichi nuclear power plants; Reactor Core Isolation Cooling; Steam condensation; Temperature behavior; Vertical temperature profile